RISIKO MENDERITA KANKER DAN NON KANKER PADA PEKERJA TERPAPAR BENZENA DI HOME INDUSTRYSEPATU KELURAHAN TAMBAK OSO WILANGUN SURABAYA - Heru Fahrudhi (Universitas Airlangga, 2017)
Work to make the shoes is a job that has a risk of harm. Equipment used in the production process such as electric heating machine / fire (oven), glue, nails and a hammer. raw materials made of fabrics, synthetic leather or plastic materials. For the gluing process uses two types of glue that glue Brands Pro ARdico yellow, white glue and glue LK brand PU-Weber, DS-DNS Bond 818. Of the various equipment and materials used, the chemicals in the manufacturing process of shoes is one of the dangers presented high. The use of chemicals can damage the health of the craftsmen shoes one of them contained in the use of glue. The general objective of this study was to analyze the level of risks to health from exposure to benzene in shoe craftsman worker. This study is an observational study conducted in the shoe industry craftsmen village Tambak Oso Wilangon Surabaya. Meanwhile, in terms of time, the type of approach used in this study is cross-sectional design of the study design using risk analysis paradigm by taking one of the other, its components, namely a risk assessment / risk assessment. The concentration of benzene measured has a value of at least 0:04 mg / m3 and a maximum of 7.44 mg / m3. The calculation result obtained RQ RQ ≤ 1 of 8 people (40%) and RQ> 1 as many as 13 people (60%) and the calculation of the ECR obtained all workers with ECR value> 10-5 as many as 20 people (100%). The conclusion from this study is there risk to workers' health effects Noncarcinogenic and all employees at risk for health effects carcinogenic.Keywords: Risk, glue, gasoline, Benzene, RQ, ECR